2003
DOI: 10.1093/humrep/deg247
|View full text |Cite
|
Sign up to set email alerts
|

ICSI and the transmission of X-autosomal translocation: a three-generation evaluation of X;20 translocation: Case report

Abstract: Published reports show that male carriers of an X-autosome translocation, which is either inherited from their mother or is de novo, are generally sterile, regardless of the position of the breakpoint in the X chromosome. We report a three-generation propagation of such a translocation in a family with a case of male factor infertility. Due to the condition of severe oligozoospermia, the proband and his wife underwent ICSI, which resulted in the birth of a normal healthy female. Cytogenetic (chromosome) analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…Azoospermia is the most common finding in male carriers of an X auto somal translocation [20], as also reported recently in a reciprocal translocation t (X;11) [21]. However a few cases with severe oligozoospermia have been reported [20], including the case reported in the present study where the patient showed a severe oligoasthenotera tozoospermia and a high frequency of unbalanced chromosome complement. Translocations involving a portion of the X chromosome have a deep impact on spermatogenesis that can lead to the formation of elon gated spermatids, but the process is remarkably ineffi cient, as indicated by the presence of a small number of spermatozoa.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Azoospermia is the most common finding in male carriers of an X auto somal translocation [20], as also reported recently in a reciprocal translocation t (X;11) [21]. However a few cases with severe oligozoospermia have been reported [20], including the case reported in the present study where the patient showed a severe oligoasthenotera tozoospermia and a high frequency of unbalanced chromosome complement. Translocations involving a portion of the X chromosome have a deep impact on spermatogenesis that can lead to the formation of elon gated spermatids, but the process is remarkably ineffi cient, as indicated by the presence of a small number of spermatozoa.…”
Section: Discussionsupporting
confidence: 85%
“…Translocations involving a portion of the X chromosome have a deep impact on spermatogenesis that can lead to the formation of elon gated spermatids, but the process is remarkably ineffi cient, as indicated by the presence of a small number of spermatozoa. In these cases ICSI techniques should be performed with the risk that X autosomal translocation can be transmitted to offspring as demonstrated by Ma et al [20] in a t(X;20) carrier.…”
Section: Discussionmentioning
confidence: 99%
“…Hitherto existing experiences with ICSI: Recently, the successful outcome of ICSI in a male carrier of an X-autosome translocation with a table of former published cases with Xautosome translocations was presented by Ma et al (2003b). They described a man with severe oligozoospermia and a maternally inherited translocation: 46,Y,t(X;20)(q10;q10).…”
Section: X-autosome Translocation In the Malementioning
confidence: 99%
“…A karyotype from umbilical cord blood was available for all studied cases. One of these infants was a reciprocal translocation carrier [46,X,t(X;20)] [Ma et al, 2003].…”
Section: To the Editormentioning
confidence: 99%